Socio-economic Consequences of Displacement and Resettlement: A Case on the Planned Oil-refinery-development Project in the Albertine Region of Uganda - Aboda, Caroline; Vedeld, Paul; Byakagaba, Patrick; Mugagga, Frank; Nabanoga, Goretti; Ruguma, Tumwine Fredrick; Mukwaya, Paul (Journal of Refugee Studies, 2021)
Millions of people are every year forcefully displaced from their places of residence and alienated from access to livelihood assets through large-scale development projects. This article examines different socio-economic consequences of displacement and resettlement caused by the planned oil-refinery site in Uganda. Household survey and interviews were employed to elicit the necessary data, analysed through descriptive statistics, logistic-regression and content analysis. Although the resettlement process exposed households to some benefits, most households were exposed to substantial risks. Over 81 per cent of households experiencing displacement lost their land and experienced reduced resource access. The results also showed significant relationships between consequences and socio-economic characteristics of respondents in that both male and female respondents had access to more and productive assets; and larger land sizes and incomes were reported to have been more affected. Also vulnerable groups including females and those with low or no education levels were more risk-prone than before the resettlement. In future development projects, the government should take into consideration the effect of the displacement and resettlement on asset access.
Keywords: Socio-economic consequences; Displacement and resettlement; Uganda